In conversation with Greg Winter. (7th October 2019) - Dhillon, Paraminder; Winter, Gregory
Abstract : Sir Gregory Winter, Research Leader Emeritus at the MRC Laboratory of Molecular Biology (LMB) in Cambridge, UK is best known for his pioneering work on humanised and human therapeutic antibodies. In 2018, he was co‐awarded the Nobel Prize in Chemistry for his revolutionary findings in this field. One year on, he discusses the impact of this award on his life and future career outlook in an interview with The FEBS Journal . Abstract : Sir Gregory Winter, Research Leader Emeritus at the MRC Laboratory of Molecular Biology (LMB) in Cambridge, UK is best known for his pioneering work on humanised and human therapeutic antibodies. Greg's research career has been entirely based in Cambridge. After studying Natural Sciences at Cambridge University, he undertook his PhD, focused on determining the amino acid sequence of bacterial tryptophanyl tRNA synthetase, at the LMB, where he remained for postdoctoral research and the ensuing establishment of his own research group. His long‐standing interest in protein and nucleic acid sequencing led to the development of techniques to 'humanise' mouse monoclonal antibodies and to make human antibodies directly, resulting in promising antibody‐based therapies for cancer and autoimmune diseases. Greg has founded three biotech companies, including Cambridge Antibody Technology and Bicycle Therapeutics. He has also received numerous awards and honours in recognition of his revolutionary work in the antibody engineering field, most notably the Nobel Prize in Chemistry in October 2018. One year on, he discusses the impact of this award on his life and future career outlook in an interview with The FEBS Journal .